The transition to non-lead rifle ammunition in Denmark: National obligations and policy considerations - Kanstrup, Niels (Ambio, 2016)
The issue of Denmark regulating use of lead-free rifle ammunition because of potential risks of lead exposure in wildlife and humans was examined from a scientific and objective policy perspective. The consequences of adopting or rejecting such regulation were identified. Denmark is obliged to examine this topic because of its national policy on lead reduction, its being a Party to the UN Bonn Convention on Migratory Species, and its role in protecting White-tailed Sea Eagles (Haliaeetus albicilla), a species prone to lead poisoning from lead ingestion. Lead-free bullets suited for deer hunting are available at comparable cost to lead bullets, and have been demonstrated to be as effective. National adoption of lead-free bullets would complete the Danish transition to lead-free ammunition use. It would reduce the risk of lead exposure to scavenging wildlife, and humans who might eat lead-contaminated wild game meat. Opposition from hunting organizations would be expected.